Effects of a conditional cash transfer programme on child nutrition in Brazil - Rômulo Paes-Sousa; Leonor Maria Pacheco Santos; Édina Shisue Miazaki (The World Health Organization, 2011)
OBJECTIVE: To examine the association between Brazil's Bolsa Familia programme (BFP), which is the world's largest conditional cash transfer programme, and the anthropometric indicators of nutritional status in children. METHODS: Using the opportunity provided by vaccination campaigns, the Brazilian government promotes Health and Nutrition Days to estimate the prevalence of anthropometric deficits in children. Data collected in 2005-2006 for 22 375 impoverished children under 5 years of age were employed to estimate nutritional outcomes among recipients of Bolsa Família. All variables under study, namely child birth weight, lack of birth certificate, educational level and gender of family head, access to piped water and electricity, height for age, weight for age and weight for height, were converted into binary variables for regression analysis. FINDINGS: Children from families exposed to the BFP were 26% more likely to have normal height for age than those from non-exposed families; this difference also applied to weight for age. No statistically significant deficit in weight for height was found. Stratification by age group revealed 19% and 41% higher odds of having normal height for age at 12-35 and 36-59 months of age, respectively, in children receiving Bolsa Familia, and no difference at 0-11 months of age. CONCLUSION: The BFP can lead to better nutritional outcomes in children 12 to 59 months of age. Longitudinal studies are needed to confirm these findings.